Delegated trade and the pricing of public and private information - Taylor, Daniel J.; Verrecchia, Robert E. (Journal of Accounting and Economics, 2015)
We extend a standard, rational expectation model of trade to incorporate the possibility of individual investors delegating their trades to an informed financial intermediary. In the presence of delegated trade, we show that a firm׳s risk premium is a function of both the firm׳s exposure to a common risk factor and idiosyncratic characteristics of the firm׳s information environment. We show that even in a large economy, priced risks can manifest in the form of both idiosyncratic firm characteristics and common risk factors; as a consequence, factor-based asset pricing tests cannot rule out that a particular risk is priced.